Method optimization for benchtop mass spectrometry imaging of lipids in Eisenia hortensis - Selby, Kendra G.; Korte, Claire E.; Phan, Lauren H.; Bressendorff, Gabriel A.; Chirchirillo, Ashley R.; Tucker, Kevin R. (Frontiers in Environmental Chemistry, 2024)
Matrix selection and application is a crucial step in obtaining meaningful results with matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI). Most instruments have a large spatial, and data with adequate spatial resolution can frequently be obtained on a benchtop instrument. The matrix application workflow has been optimized for the imaging of the earthworm (Eisenia hortensis), after exposure to various statins, a class of blood lipid-lowering agents. Lipids are nonpolar, often neutral molecules, making them difficult to ionize, and heightening the need for matrix optimization. The matrices 2,5-dihydroxybenzoic acid (DHB), α-cyano-4-hydroxycinammic acid (CHCA), 1,5-diaminonaphthalene (DAN), and 3,5-dimethoxy-4-hydroxycinnamic acid (sinapinic acid; SA) were studied. Samples were also washed in the ammonium salts of acetate, bicarbonate, formate, sulfate, or water as a control to enhance ionization and improve spatial resolution. A successful matrix for MSI is one that demonstrates homogenous tissue coverage, ionization of the analytes of interest, and does not require excessive laser power for ionization. All matrices showed sufficient tissue coverage; however, CHCA yielded unambiguous images of cholesterol and yielded sufficient signal over the lipid mass range (400-1000 m/z), indicating that it successfully ionized endogenous lipids. Following additional optimization, the application of 50 mL of 10 mg/mL CHCA following a 5 second salt ammonium sulfate salt wash proved most successful for improving lipid ionization and enhancing spatial resolution.